2008
DOI: 10.1111/j.1360-0443.2008.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

The shifting pattern of cause‐specific mortality in a cohort of human immunodeficiency virus‐infected and non‐infected injecting drug users

Abstract: Cardiovascular and cancer mortality are increasing among IDUs, but the increases are not related to HIV infection. We have not found a link between highly active antiretroviral therapy (HAART) introduction and increases in mortality for specific causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…We confirm the findings of earlier studies which emphasize that successful ART is possible among former or current IDUs, and particularly effective in the setting of stable opiate substitution [5,11,18,31,32,[46][47][48]. As a consequence, ART should not be withheld from this patient group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We confirm the findings of earlier studies which emphasize that successful ART is possible among former or current IDUs, and particularly effective in the setting of stable opiate substitution [5,11,18,31,32,[46][47][48]. As a consequence, ART should not be withheld from this patient group.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in vitro and animal studies found immunosuppressive effects of opiates, cocaine and other illicit substances [24][25][26][27][28][29][30]. Since 1996, combination ART has largely determined the outcome of HIV infection in patients with access to care [16], and mortality was found to be substantially reduced after the introduction of potent ART also among IDUs [31][32][33]. Therefore, drug addiction treatment programmes, which make access to somatic care possible, appear to be an important prerequisite for improved outcome of ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Most of the causes of death associated with the greatest excess mortality, including infection, "other" causes and mental or behavioural disorders, were consistent with major causes of death identified in other studies. 14,15,[18][19][20][21][22][23] Of note was the elevated excess mortality related to respiratory disease (primarily pneumonia). A study involving drug users entering treatment in Rome, Italy, reported a similar SMR of 10.2 for respiratoryrelated death.…”
Section: Discussionmentioning
confidence: 99%
“…In injecting drug users, the prevalence of HIV is low (<1% in heterosexuals), whereas the prevalence of hepatitis C is high (50–60%) 7. However, one of the consequences of the increased longevity of opioid-dependent people is the attendant risk of age-related health conditions, including cancer 8. The OST agents themselves are not considered risk factors for cancer as murine studies indicate they are not carcinogenic 9 10…”
Section: Introductionmentioning
confidence: 99%